Effect of crosslinkers on bond strength stability of fiber posts to root canal dentin and in situ proteolytic activity - Alonso, Juliana R.L. [UNESP]; Basso, Fernanda G. [UNESP]; Scheffel, Débora L.S. [UNESP]; de-Souza-Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Elsevier, 2018)
Statement of problem: Improved stability of the adhesive interface can be obtained using crosslinkers. However, research on the use of crosslinkers in root dentin is lacking. Purpose: The purpose of this in vitro study was to evaluate the effect of crosslinkers on the proteolytic activity of root dentin and on the bond strength of resin-cemented fiber posts. Material and methods: Single root canals were obtained from premolars (n=48) and endodontically treated before being divided into 4 groups: deionized water (control), 0.5 mol/L carbodiimide, 5% proanthocyanidin, or 5% glutaraldehyde. After removing the canal sealer, the dentin was etched with phosphoric acid, followed by water rinsing and the application of the crosslinkers for 60 seconds. Fiber posts were cemented using an adhesive (Single Bond 2) and resin cement (RelyX ARC). The roots were then transversally sectioned to obtain 1 mm thick specimens from the cervical, middle, and apical thirds and then aged for 24 hours or 9 months. Nine roots per group were used for the push-out test and 3 for determining the proteolytic activity of the root dentin by in situ zymography. Bond strength data were submitted to a mixed-model ANOVA and Bonferroni tests (α=.05). Results: Only proanthocyanidin negatively affected the 24-hour bond strength. After 9 months, a significant decrease in bond strength was seen for all groups, except for the crosslinked treated specimens from the cervical third of the root canal. Intense gelatinolytic activity was detected in the control group after 24 hours but was inhibited in the crosslinker-treated groups. Proteolytic activity was also not detected after 9 months for the groups treated with the crosslinkers, irrespective of the root canal third. Conversely, proteolytic activity increased for the specimens from the control group. Conclusions: Although no proteolytic activity was detected in the hybrid layers along the entire root canal, dentin biomodification with crosslinkers was effective in preventing bond strength loss only in the cervical third.